2014
DOI: 10.1177/0956797613516148
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Differences in Subjective Well-Being Predict Extraordinary Altruism

Abstract: Altruistic kidney donation is a form of extraordinary altruism, the antecedents of which are poorly understood. Although well-being is known to increase the incidence of prosocial behaviors and there is significant geographical variation in both well-being and altruistic kidney donation in the United States, it is unknown whether geographical variation in well-being predicts the prevalence of this form of extraordinary altruism. We calculated per capita rates of altruistic kidney donation across the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 31 publications
(56 reference statements)
2
33
0
1
Order By: Relevance
“…These characteristics seem applicable to the pandemic, wherein the fear of infection has co-occurred with that of losing one's job and/or access to essential goods like medication, food, or even toilet paper. However, the notion of a fundamentally selfish human nature is called into question by the ubiquitous nature of everyday altruism in modern societies (Mattis et al, 2009;Sisco & Weber, 2019), and by instances of extraordinary altruism in highly risky (e.g., heroic rescues; https://www.carnegiehero.org/) or costly scenarios (e.g., non-directed organ donation; Brethel-Haurwitz & Marsh, 2014). Importantly, it has been suggested that challenging contexts may in fact promote rather than hinder altruistic motivation (Buchanan & Preston, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics seem applicable to the pandemic, wherein the fear of infection has co-occurred with that of losing one's job and/or access to essential goods like medication, food, or even toilet paper. However, the notion of a fundamentally selfish human nature is called into question by the ubiquitous nature of everyday altruism in modern societies (Mattis et al, 2009;Sisco & Weber, 2019), and by instances of extraordinary altruism in highly risky (e.g., heroic rescues; https://www.carnegiehero.org/) or costly scenarios (e.g., non-directed organ donation; Brethel-Haurwitz & Marsh, 2014). Importantly, it has been suggested that challenging contexts may in fact promote rather than hinder altruistic motivation (Buchanan & Preston, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1 In experimental research, it has also been shown that people often reduce others' payoffs at personal cost when the cost imposed on others is larger than that incurred by the decision maker (e.g., Zizzo & Oswald 2001, Abbink et al 2010, Abbink & Herrmann 2011, Brañas-Garza et al 2014, which is consistent with individuals having a preference for increasing their relative standing. However, the opposite is often observed as well: people are willing to sacrifice their own payoffs in order to increase the welfare of others (e.g., Piliavin & Charng 1990, Forsythe et al 1994, Ledyard 1995, Camerer 2003, Staffiero et al 2013, Brethel-Haurwitz & Marsh 2014, which could be modeled as if others' payoffs enter positively into the individuals' utility functions. 2 Based on all this evidence, we shall assume that individuals aim at increasing their relative standing within the group they belong to (i.e., they are "competitive") 3 but also at enhancing the performance of the group, or social efficiency (i.e., they are "cooperative"; see McClintock 1972, Van Lange et al 1997, Charness & Rabin 2002.…”
Section: Introductionmentioning
confidence: 99%
“…intuitive) processes. Finally, a recent study examined the extremely costly behavior of kidney donation (albeit not from a dual process perspective) and found that across the United States, kidney donation was more likely in areas with higher subjective well-being [92] .…”
Section: Introductionmentioning
confidence: 99%